1978
DOI: 10.1073/pnas.75.2.905
|View full text |Cite
|
Sign up to set email alerts
|

Lucibufagins: Defensive steroids from the fireflies Photinus ignitus and P. marginellus (Coleoptera: Lampyridae)

Abstract: Feeding tests with thrushes (Hylocichia spp.) led to the isolation of three novel steroid pyrones from fireflies (Photinus ignitus and P. marginellus) responsible, in part at least, for the unpalatability of these insects to the birds. The term lucibufagin is coined for these steroidal pyrones. The closest known relatives of lucibufagins are the familiar cardiotonic bufadienolides, found in certain toads and plants. It had previously been suspected that fireflies-the familiar luminescent beetles of the famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 17 publications
0
70
0
Order By: Relevance
“…Eisner et al [15] postulated that lampyrids produce these steroid-related molecules from ingested cholesterol, a nutrient required for growth ofspiroplasmas and mycoplasmas. Spiroplasmas are frequently present in other insects [ 19] that possess cardenolides (e.g., danaid butterflies and chrysomelid beetles [ 15]) or that have cholesterol-rich diets (e.g., tabanid flies, mosquitoes, and ticks). Determination of a causative relationship between this added sterol dependence and the high frequency of associations of these insects with spiroplasmas and mycoplasmas would be important to our understanding of the role of these microbes in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eisner et al [15] postulated that lampyrids produce these steroid-related molecules from ingested cholesterol, a nutrient required for growth ofspiroplasmas and mycoplasmas. Spiroplasmas are frequently present in other insects [ 19] that possess cardenolides (e.g., danaid butterflies and chrysomelid beetles [ 15]) or that have cholesterol-rich diets (e.g., tabanid flies, mosquitoes, and ticks). Determination of a causative relationship between this added sterol dependence and the high frequency of associations of these insects with spiroplasmas and mycoplasmas would be important to our understanding of the role of these microbes in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Many members exhibit unique physiological characteristics, including luminescence. They also release large amounts of steroid related cardenolides (lucibufagins [15,17,28]) by reflex bleeding [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the Lampyridae, many species exhibit reflex bleeding, and the excreted fluid is stinky, distasteful and repellent to predators (Lloyd, 1973;Ohba and Hidaka, 2002). Eisner et al (1978) demonstrated that fireflies possess defensive steroids in effective quantities to deter predation. Lizards, birds and mice quickly learn to associate bioluminescence with a distasteful organism (Underwood et al, 1997;Matthysen, 1999, 2003;Knight et al, 1999).…”
Section: Fireflies (Lampyridae)mentioning
confidence: 99%
“…This bug discharges a mixture of pregnanes in which desoxycorticosterone is the main component (12). A family of much more highly functionalized steroids, the lucibufagins, serves to render some species of firefly (lampyrid beetles) unpalatable to predatory spiders and birds (13)(14)(15) …”
Section: Arthropod Chemical Defensesmentioning
confidence: 99%